Analysis of the Effect of Southeast Asia Stock Index on the Indonesia Stock Exchange (IDX) Composite - Dadang Prasetyo Jatmiko (International Journal of Scientific Multidisciplinary Research, 2023)
This study was conducted with the aim of analyzing and knowing the development of the composite stock price index in the Southeast Asia region in relation to the size of the Indonesia Stock Exchange (IDX) Composite as well as determining the effect of the three Southeast Asia Stock Indexes, either partially or simultaneously on the Indonesia Stock Exchange (IDX) Composite. The three Southeast Asia Stock Indexes are the Bursa Malaysia Index (Malaysia), the Philippine Stock Exchange Index (Philippine) and the Straits Times Index (Singapore). The simple sampling method used was by collecting data for 48 months from January 2019 to December 2022. The data analysis used to test the research hypothesis was SPSS 15 (Statistical Product and Service Solution version 15.0), namely multiple linear regression. The results show that the effect of the three Southeast Asia Stock Indexes partially or simultaneously has a significant effect on the Indonesia Stock Exchange (IDX) Composite